QUANTITATIVE DIFFERENCES WITHIN ANTHROPOMETRIC SPACE WITH FEMALE STUDENTS AT HIGH SCHOOL - Viktor Mitrevski; Georgi Georgiev; Naser Rashiti; Fadil Nika (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The aim of this research is to determine the differences within anthropometric space with female students attending the regular class activity in physical education at school, the activities being held in different working conditions. Depending on these conditions the female students are divided into three (3) sub-examples, or the research includes a total of 183 entities. The analyses of results makes use of seven anthropometric parameters four of which treat the circular dimension and three treat subcutaneous fatty tissue. In order to determine differences between the three groups of female students according to the working conditions in class, the following analyses are used: univariate analysis of variance (ANOVA), t-test, and multivariate analysis of variance (MANOVA). The obtained data pointsat statistically significant differences between the groups within the whole space of anthropometric analysis. Arithmetic means are analysed between the groups with regard to all variables, and between the arithmetic means statistically significant differences are only determined with the variable of average volume of stomach (ASOS), whereas with the rest of variables statistically significant differences are not marked.